Pengaruh Implementasi Kurikulum Outcome Based Education (OBE) terhadap Kemampuan Problem Solving Mahasiswa - Yunus, Yuliawati; Maksum, Hasan; Waskito, Waskito (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This study examines the effect of implementing the Outcome Based Education (OBE) curriculum on the problem-solving abilities of Management Study Program students at the Faculty of Economics and Business, a university in Padang, Indonesia, focusing on the Information and Computer Technology course. The subjects were 60 students, and a correlational quantitative approach was used. Data analysis included descriptive analysis, normality test, linearity test, and linear regression test. Results showed normally distributed and linear data. The F-test yielded a value of 15.918 with a significance level of 0.000<0.005, indicating a significant influence of the OBE curriculum (X) on problem-solving ability (Y). The R Squared value of 0.215 indicates that the OBE curriculum accounts for 21.5% of the variance in students' problem-solving abilities, excluding other factors.   Keywords: Ability; curriculum; information and computer technology; outcome based education; problem solving